Analysis of Market Segmentation and Targeting on Market Growth Mediated by Marketing Ability on Android Products in Banten - Asep Supriadi (West Science Business and Management, 2023)
This research delves into the Android product market in Banten, aiming to analyze the interplay between market segmentation, targeting strategies, marketing ability, and market growth. A sample of 287 participants provided insights into demographic characteristics, technology adoption patterns, and income levels. Employing Structural Equation Modeling with Partial Least Squares (PLS-4), the study revealed significant direct effects of market segmentation and targeting strategies on market growth. Marketing ability emerged as a crucial mediator, indicating its pivotal role in translating segmentation and targeting efforts into tangible market outcomes. The model demonstrated a strong fit, supported by high goodness-of-fit and normed fit indices. R² and Q² metrics underscored the model's explanatory power and predictive relevance for market growth. The findings offer actionable insights for businesses, emphasizing the importance of tailored strategies and the enhancement of marketing capabilities for sustained market growth.